2022
DOI: 10.3389/fnut.2022.820010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Quinoa Seed Fatty Acid Profile Under Heat Stress Field Conditions

Abstract: The nutritional quality of quinoa is often related to the high protein content of their seeds. However, and despite not being an oilseed crop, the oil composition of quinoa seeds is remarkable due to its profile, which shows a high proportion of polyunsaturated fatty acids (PUFAs), particularly in essential fatty acids such as linoleic (ω-6) and α-linolenic (ω-3). In line with this, this study aimed at evaluating the effect of elevated temperatures on the oil composition of different quinoa cultivars grown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 83 publications
5
9
1
Order By: Relevance
“…Interestingly, PUFAs decline differed between genotypes. The different evolution patterns of fat content between genotypes were expected, since the initial content and the fatty acid profile were also very different (Figures 3A,B), as previously reported when studying different quinoa genotypes (29). In F16, the targeted fatty acid was α-linolenic acid (C18:3), while in Duquesa seeds there was a reduction of linoleic acid (C18:2) over time, the main fatty acid present in quinoa seeds (Figure 3B) (29,73).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Interestingly, PUFAs decline differed between genotypes. The different evolution patterns of fat content between genotypes were expected, since the initial content and the fatty acid profile were also very different (Figures 3A,B), as previously reported when studying different quinoa genotypes (29). In F16, the targeted fatty acid was α-linolenic acid (C18:3), while in Duquesa seeds there was a reduction of linoleic acid (C18:2) over time, the main fatty acid present in quinoa seeds (Figure 3B) (29,73).…”
Section: Discussionsupporting
confidence: 79%
“…The different evolution patterns of fat content between genotypes were expected, since the initial content and the fatty acid profile were also very different (Figures 3A,B), as previously reported when studying different quinoa genotypes (29). In F16, the targeted fatty acid was α-linolenic acid (C18:3), while in Duquesa seeds there was a reduction of linoleic acid (C18:2) over time, the main fatty acid present in quinoa seeds (Figure 3B) (29,73). The relation between these two fatty acids is also important in human diets, since they are the main ω-6 (linoleic acid) and ω-3 (α-linolenic acid) found in our diet and they can impact the ω-6/ω-3 ratio, which is recommended to be between 5:1 and 10:1 in order to reduce the risk of cancer and cardiovascular diseases (74).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…To the best of our knowledge, no study has yet identified changes in the lipidome and related metabolic pathways in camellia oil affected by insects. More importantly, unlike previous reports on oil fruit containing only one oilseed, oil tea fruit contains multiple oilseeds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in a single fruit, implying that infested and non-infested oilseeds will coexist in the same fruit. However, no previous research has been conducted on the differences in lipid composition of non-infested oilseeds from infested fruit and non-infested fruit.…”
Section: Introductioncontrasting
confidence: 61%
“…Seed oils are rich in a variety of nutrients including dietary fats and phytochemicals, and they have medical and commercial applications (1,2). Lipids are the most abundant component of seed oils, and their composition has a direct impact on the nutritional quality of the seed oil, which is critical to human health (3,4). In the past, the main focus of seed oil lipid studies has been on oil yield and the fatty acid composition of the extracted lipids (5).…”
Section: Introductionmentioning
confidence: 99%